Effect of Speed and Balance Against Soccer Dribbling on Out of School Students of SD Negeri 78 Palembang - Rohman, Taufikur; Akhbar, M Taheri (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study is to determine the effect of speed and balance training on soccer dribbling performance in extracurricular activities in SD Negeri 78 Palembang. The exploratory research method used was a one-group pre-test and post-test design experiment. With a one-group pre-test and post-test design. The population in this research was students who were involved in football extracurricular activities, the sample in this research was 30 people. The research instrument used was the soccer dribbling test. The treatment in this study took the form of agility and balance exercises performed for 6 weeks at a training frequency of 3 times per week. Test the performance using the experimental method with the results of the characteristic “t test” α = 0.05, obtained t-count = (23.6), while t-table = (1.70), l, so that Ha can be accepted, while HO rejects. According to the findings of the research that Ha is acceptable, then agility and balance exercises affect the improvement of soccer dribbling. The implication of this research is that agility and balance exercises can be used as a type of exercise to improve soccer dribbling.